Pengaruh Konflik Kerja dan Semangat Kerja Terhadap Kinerja Pegawai Pada Kantor Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sikka - Elisabeth Nona Selvin; Antonius Philippus Kurniawan; Victor Eko Transilvanus (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2023)
This study aims to (1) To find out the description of Employee Performance, Work Conflict and Work Enthusiasm at the Office of the Population and Civil Registration Office of Sikka Regency (2) To find out the effect of Work Conflict on employee performance at the Office of Population and Civil Registration Office of Sikka Regency both simultaneously or partial. The population in this study were 57 employees who worked in Sikka Regency. The sample used is saturated sample technique. Data is collected through census or saturated sampling. Data were collected through questionnaires and analyzed using a descriptive method, namely multiple linear regression. Hypothesis testing through the F test and t test. The results of the descriptive analysis show that the variables of employee performance, work conflict and work morale are quite good. The results of the t test show that the variables of work conflict and work enthusiasm have a significant value on employee performance. The results of the F test show that the variables of work conflict and work enthusiasm simultaneously have a significant effect on employee performance. The coefficient of determination is 0.498, which means that the contribution of the work conflict and work morale variables to employee performance is 24.8% at the population and civil registration office in the Sikka district.